Chemical, Mineralogical, and Refractory Characterization of Kaolin in the Regions of Huayacocotla-Alumbres, Mexico - L. M. Romero-Guerrero; R. Moreno-Tovar; A. Arenas-Flores; Y. Marmolejo Santillán; F. Pérez-Moreno (Advances in Materials Science and Engineering)
In the present work, the chemical, mineralogical, refractory, and microstructural characterizations of kaolinites from the Huayacocotla-Alumbres region, which is between Veracruz and Hidalgo border, by X-ray diffraction (XRD), polarization optical microscopy (POM), scanning electron microscopy (SEM), refractoriness proof (pyrometric cone equivalent), and thermogravimetric analysis (TGA) were carried out. The analysis by POM showed that the kaolinization degree in this region is variable due to the presence of primary minerals, such as plagioclase, feldspar, and quartz. Additionally, hydrothermal alteration of the epithermal type was determined by oxidation of sulfides (pyrite and galena) and chlorite association. With the X-ray diffraction technique, andalusite and kaolinite were identified as the majority phases in Huayacocotla and quartz was identified as the majority phase in Alumbres. The minority phases, such as dickite, kaolinite, and cristobalite, were observed in both zones. The SEM technique was useful in the determination of the morphology of kaolinite and impurities of Na, Mg, K, and Fe of the complex clay illite-andalusite-dickite group. Thermogravimetric analysis was useful to discover the decomposition temperature and reveal the significant difference between 400 and 800°C, which showcases the greatest mass loss due to dehydration and carbonates decomposition. The mullite phase was detected at approximately 1000°C in the kaolin samples. The refractoriness tests were important to determine the stability temperature of kaolin, which is between 1300 and 1600°C. This stability temperature makes it feasible to use the kaolin as a refractory material for both low and high temperatures. The variables that affect the kaolin stability temperature were determined by principal components with the XLSTAT free program.